Kinerja Pemerintah dalam Rehabilitasi dan Rekonstruksi Kawasan Rawan Bencana (KRB) di Kabupaten Magelang - Khoirunnisa, Syifa Azmy; Warsono, Hardi; Suryaningsih, Margaretha (Journal of Public Policy and Management Review, 2014)
Rehabilitation and reconstruction is one effort contained in the disaster management cycle after mitigation and emergency response. Rehabilitation and reconstruction of post-disaster to be a need of the affected community disaster.  Disaster management organizers in Magelang District in general is Badan Penanggulangan Bencana Daerah (BPBD) Kabupaten Magelang, and in particular for the rehabilitation and reconstruction activities organized  by sector of Rehabilitation and Reconstruction.  BPBD Kabupaten Magelang has a vision "realize Magelang Regency responsive, fast, accurate, and resilient in the face of disaster".   The purpose of this study is to identify the performance of BPBD Kabupaten Magelang as the government in rehabilitating and reconstructing disaster-prone areas eruption of Mount Merapi in 2010. And identify determinants effectiveness of the achievement target of rehabilitation and reconstruction. Performance indicators views of the four indicators that have been formulated, namely effectiveness, efficiency, fairness, and responsiveness. The deciding factor the effectiveness of target  achievement of the three factors that have implications for the performance, namely training, work discipline, and job satisfaction. This study used a qualitative descriptive type with informants of the implementers of  rehabilitation and reconstruction post-disaster of the eruption of Mount Merapi in 2010 and from beneficiaries of rehabilitation and reconstruction. The results of overall this study is performance of BPBD Kabupaten Magelang n rehabilitating and reconstructing been not good when viewed from four performance indicators. Then the three factors that have implications for the performance, namely training, work discipline, and job satisfaction shown to affect the effectiveness the achievement of targets or performance of rehabilitation and reconstruction.